Foveal Sensitivity and Morphology in Major and Macular Branch Retinal Vein Occlusion - Noma, Hidetaka (Bentham Open, 2012)
PURPOSE: To determine whether foveal thickness, foveal volume, visual acuity, and foveal sensitivity after intravitreal injection of triamcinolone acetonide (IVTA) are influenced by the extent of occlusion (major versus macular branch retinal vein occlusion (BRVO)). MATERIALS AND METHODOLOGY: In this interventional case series, 22 eyes of 22 BRVO patients with macular oedema were treated by IVTA. Patients were divided into 2 groups according to the site of occlusion, with the Major group having occlusion of a major retinal vein and the Macular group having occlusion of a macular venule. Foveal sensitivity was measured by microperimetry before IVTA and 3 and 6 months after IVTA. Visual acuity was converted to logarithm of the minimal angle of resolution (logMAR) values. Foveal thickness and macular volume were measured by optical coherence tomography before IVTA and 3 and 6 months after IVTA. RESULTS: Foveal thickness and foveal volume showed significant improvement from before to 3 and 6 months after IVTA in both groups (all P<0.001). Visual acuity also showed significant improvement from before to 3 and 6 months after IVTA in both groups (P=0.001 and P=0.022, respectively). Moreover, foveal sensitivity was significantly improved from before to 3 and 6 months after IVTA in the Major group (P<0.001). Foveal sensitivity also increased from before to 3 and 6 months after IVTA in the Macular group, but not significantly. There were no significant differences in the trend profiles of foveal thickness, foveal volume, visual acuity, and foveal sensitivity between the Major and Macular groups. CONCLUSIONS: These results suggest that IVTA may be effective for improving foveal morphology, visual acuity, and foveal sensitivity in BRVO patients regardless of the site of occlusion.